Occurrence of two Krsticiella species in Beringia suggests this genus is a Cenozoic relict. Issue 2 (3rd April 2019) - Potapova, Marina G.
Abstract : The genus Krsticiella Levkov was previously known only from the basins of Lakes Ohrid and Prespa, and from Lake Baikal. Examination of type materials of diatoms originally described by Niels Foged from the North Slope of Alaska revealed that Navicula lenis Foged and N. meadeensis Foged belong to Krsticiella, to which they are formally transferred here. One of these species, K. lenis, is also found in thermokarst tundra lakes of the Kolyma Lowland in Northeastern Siberia. Several illustrations in previously published floras of Pliocene and Pleistocene diatoms of Eurasia indicate wider past distributions of Krsticiella species. The current restriction of this genus to non-glaciated regions of the Arctic and large ancient lakes in temperate zone indicates that it is a Cenozoic relict.